Healthcare access and attitudes towards telehealth during the early phase of the COVID‐19 pandemic among an Australian cohort with inflammatory arthritis. Issue 5 (27th May 2021) - Rischin, Adam; Liew, David; Black, Rachel; Fletcher, Ashley; Buchbinder, Rachelle; Lassere, Marissa; March, Lyn; Robinson, Philip C.; Hill, Catherine; ,
Abstract: Community restrictions due to COVID‐19 have changed healthcare, including increased telehealth use. During the early pandemic phase, a cohort of Australian patients with inflammatory arthritis was surveyed. Self‐reported access to healthcare was maintained and physical health was more likely to be self‐rated poorly than mental health. There was a high level of support for telehealth during and after the pandemic.